Improving Reading Skills in A2 Level Students - Farinango Carvajal, Sandra Elizabeth; Campoverde López, Johnny Segundo; Bonilla Tenesaca, Josue Reinaldo (Arandu UTIC, 2025)
Today, the use of English has become an essential tool to open many doors at a professional level. According to the Common European Framework of Reference for Languages, there are six proficiency levels that can facilitate teaching methods and assessment, regrouped in Basic User, Independent User, and Proficient User. However, the model of the four skills (listening, reading, speaking and writing) implies additional challenges for teachers in their classrooms when dealing with students at the A2 level. Consequently, this article has the general objective of analyzing different strategies and tips used to improve reading skills in A2 level students according to the specialized literature and the data collected from instruments applied in the analyzed context. In order to achieve this goal, research methods such as literature systematization, deductive and inductive approaches in the study of international and national authors, as well as surveys are used. The main authors and articles used for this literature review have been selected from specialized journals and publications found in Scholar Google during the period 2021-2025. The sample involved 36 participants, 31 students and 5 teachers selected through a convenience sampling method. The results demonstrate that a combination of structured reading techniques and interactive learning experiences effectively enhances reading proficiency among A2 students.